Resistance to endoparasites in small ruminants: Genetic considerations - Woolaston, R.R. (International Livestock Centre for Africa, 1991)
This paper focusses on within-breed genetic variation in resistance to endoparasites in the Australian Merino. It stresses possible differences in the Merino resistance, simply because of different history of management. The Australian Merino was introduced into Australia 200 years ago. It has almost entirely developed in that environment, i.e., it has been exposed to different methods of parasite control drenching, and there has been very little natural selection for resistance in this breed over recent years. However, the Australian Merino has been studied for over 20 years for genetic variation in parasite resistance. Genetic variation in resistance to endoparasites has been studied in five flocks in Armidale, and on flocks in New Zealand and Fiji. They were assessed using faecal egg count following artificial infection. The first flock includes lines of medium-wool peppins, and the others are based on fine and fine-medium Merinos. The work with these flocks showed that the heritability of resistance to endoparasites is measurable and that resistance is not genetically correlated with such production traits as fertility, body weight, fibre diameter and wool weight.